Is there any association between low level of serum nesfatin-1 and fibromyalgia syndrome? - Birşen BİLGİCİ,; Yeşim AKYOL,; Yasemin ULUS,; Sebati Sinan ÜRKMEZ,; Ömer KURU, (Archives of Rheumatology, 2021)
Objectives: This study aims to investigate the relationship between serum level of nesfatin-1 and fibromyalgia syndrome (FMS) clinical parameters such as pain severity, disease activity, fatigue, emotional state, and sleep quality. Patients and methods: Forty-six female patients with FMS (median age 40 years; range, 18 to 53 years) and 46 healthy female controls (median age 36 years; range, 19 to 52 years) were included in the study. Severity of pain, disease activity, fatigue, sleep quality, and emotional status were evaluated by visual analog scale, Fibromyalgia Impact Questionnaire, Multidimensional Assessment of Fatigue (MAF), Pittsburgh Sleep Quality Index (PSQI), Beck Depression Inventory (BDI), and Beck Anxiety Inventory (BAI), respectively. Serum nesfatin-1 concentrations (pg/mL) were measured by enzyme-linked immunosorbent assay method. Results: There was no significant difference with respect to demographic characteristics between the FMS patients and healthy controls. When clinical parameters were compared, MAF, BDI, BAI, and PSQI scores were significantly higher in FMS patients than controls (p<0.05). Serum nesfatin-1 concentration was significantly lower in patients with FMS (p<0.05). When compared to the FMS patients without anxiety, serum nesfatin-1 concentration was significantly increased in FMS patients with anxiety (p<0.05). Serum nesfatin-1 concentration was positively correlated with BAI scores in patients with FMS (p<0.05). Conclusion: Low nesfatin-1 serum levels may contribute to pathological changes in FMS. In addition, nesfatin-1 may also be involved in the mediation of anxiety-related responses in FMS.